Growth performance, immune response, and resistance of Nile tilapia fed paraprobiotic Bacillus sp. NP5 against Streptococcus agalactiae infection - Aldy Mulyadin; Widanarni Widanarni; Munti Yuhana; Dinamella Wahjuningrum (Jurnal Akuakultur Indonesia)
ABSTRACT